Do different rates of gene flow underlie variation in phenotypic and phenological clines in a montane grasshopper community? - Rachel A. Slatyer; Sean D. Schoville; César R. Nufio; Lauren B. Buckley (Ecology and Evolution, 2020)
Abstract Species responses to environmental change are likely to depend on existing genetic and phenotypic variation, as well as evolutionary potential. A key challenge is to determine whether gene flow might facilitate or impede genomic divergence among populations responding to environmental change, and if emergent phenotypic variation is dependent on gene flow rates. A general expectation is that patterns of genetic differentiation in a set of codistributed species reflect differences in dispersal ability. In less dispersive species, we predict greater genetic divergence and reduced gene flow. This could lead to covariation in life‐history traits due to local adaptation, although plasticity or drift could mirror these patterns. We compare genome‐wide patterns of genetic structure in four phenotypically variable grasshopper species along a steep elevation gradient near Boulder, Colorado, and test the hypothesis that genomic differentiation is greater in short‐winged grasshopper species, and statistically associated with variation in growth, reproductive, and physiological traits along this gradient. In addition, we estimate rates of gene flow under competing demographic models, as well as potential gene flow through surveys of phenological overlap among populations within a species. All species exhibit genetic structure along the elevation gradient and limited gene flow. The most pronounced genetic divergence appears in short‐winged (less dispersive) species, which also exhibit less phenological overlap among populations. A high‐elevation population of the most widespread species, Melanoplus sanguinipes, appears to be a sink population derived from low elevation populations. While dispersal ability has a clear connection to the genetic structure in different species, genetic distance does not predict growth, reproductive, or physiological trait variation in any species, requiring further investigation to clearly link phenotypic divergence to local adaptation.